RNA-seq analysis of early enteromyxosis in turbot (Scophthalmus maximus): new insights into parasite invasion and immune evasion strategies - Ronza, Paolo; Robledo, Diego; Bermúdez, Roberto; Losada, Ana Paula; Sitjà-Bobadilla, Ariadna; Quiroga, María Isabel; Martínez, Paulino (International Journal for Parasitology, 2016)
Enteromyxum scophthalmi, an intestinal myxozoan parasite, is the causative agent of a threatening disease for turbot (Scophthalmus maximus, L.) aquaculture. The colonisation of the digestive tract by this parasite leads to a cachectic syndrome associated with high morbidity and mortality rates. This myxosporidiosis has a long pre-patent period and the first detectable clinical and histopathological changes are subtle. The pathogenic mechanisms acting in the early stages of infection are still far from being fully understood. Further information on the host–parasite interaction is needed to assist in finding efficient preventive and therapeutic measures. Here, a RNA-seq-based transcriptome analysis of head kidney, spleen and pyloric caeca from experimentally-infected and control turbot was performed. Only infected fish with early signs of infection, determined by histopathology and immunohistochemical detection of E. scophthalmi, were selected. The RNA-seq analysis revealed, as expected, less intense transcriptomic changes than those previously found during later stages of the disease. Several genes involved in IFN-related pathways were up-regulated in the three organs, suggesting that the IFN-mediated immune response plays a main role in this phase of the disease. Interestingly, an opposite expression pattern had been found in a previous study on severely infected turbot. In addition, possible strategies for immune system evasion were suggested by the down-regulation of different genes encoding complement components and acute phase proteins. At the site of infection (pyloric caeca), modulation of genes related to different structural proteins was detected and the expression profile indicated the inhibition of cell proliferation and differentiation. These transcriptomic changes provide indications regarding the mechanisms of parasite attachment to and invasion of the host. The current results contribute to a better knowledge of the events that characterise the early stages of turbot enteromyxosis and provide ...